THE IMPACT OF THE STAPHYLOCOCCUS AUREUS INFECTION ON THE EVOLUTION OF CHILDREN WITH CYSTIC FIBROSIS FROM A REGIONAL CENTRE IN NORTH-EASTERN ROMANIA - Dana-Teodora; Mihaela Moscalu; Gabriela Coman; Laura Florescu; Laura-Mihaela Trandafir (Amaltea Medical Publishing House, 2014)
Introduction. Chronic bacterial infections and - often - acute infectious exacerbations are characteristic to the lung disease of the cystic fi brosis (CF). The objective of this study was to identify children with CF and Staphylococcus aureus infection and quantify the impact of this infection on their clinical status. Material and methods. A prospective study was carried out during 3 years on a batch of 37 children with CF registered in the records of the Regional Monitoring Centre of the 3rd Clinic of Pediatrics of Iasi, Romania. In these patients, we searched for the presence of S. aureus, the prevalence of methicillin-resistant S. aureus (MRSA) strains, the impact of the chronic infection with MRSA on the lung function concomitant with the presence of severity elements in CF. Results. 22 of the 37 patients with CF had positive culture for S. Aureus; at 9 of them was isolated MRSA and 5 had chronic infection. The MRSA positive group of patients presented signifi cantly lower values of the FEV1, a more poor nutritional status, severe bronchiectases, a larger number of pulmonary exacerbations and implicitly hospitalizations, pancreatic insuffi ciency in most cases and a higher degree of association with the F508del genotype. Conclusions. S. aureus remains an important pathogen in CF. Due to its high pathogeny, S. aureus and especially the MRSA strains can contribute to an unfavourable clinical evolution.